Impact of neoadjuvant therapy on post‐operative pancreatic fistula: a systematic review and meta‐analysis. Issue 11 (17th May 2020) - Kamarajah, Sivesh K.; Bundred, James R.; Boyle, Charles; Oo, June; Pandanaboyana, Sanjay; Loveday, Benjamin
Abstract: Introduction: The use of neoadjuvant therapy (NAT) for pancreatic cancer is increasing, although its impact on post‐operative pancreatic fistula (POPF) is variably reported. This systematic review and meta‐analysis aimed to assess the impact of NAT on POPF. Methods: A systematic literature search until October 2019 identified studies reporting POPF following NAT (radiotherapy, chemotherapy or chemoradiotherapy) versus upfront resection. The primary outcome was overall POPF. Secondary outcomes included grade B/C POPF, delayed gastric emptying (DGE), post‐operative pancreatic haemorrhage (PPH) and overall and major complications. Results: The search identified 24 studies: pancreatoduodenectomy (PD), 19 studies (n = 19 416) and distal pancreatectomy (DP), five studies (n = 477). Local staging was reported in 17 studies, with borderline resectable and locally advanced disease comprising 6% (0–100%) and 1% (0–33%) of the population, respectively. For PD, any NAT was significantly associated with lower rates of overall POPF (OR: 0.57, P < 0.001) and grade B/C POPF (OR: 0.55, P < 0.001). In DP, NAT was not associated with significantly lower rates of overall or grade B/C POPF. Conclusion: NAT is associated with significantly lower rates of POPF after PD but not after DP. Further studies are required to determine whether NAT should be added to POPF risk calculators. Abstract : Neoadjuvant therapy is associated with significantly lower rates of post‐operative pancreatic fistula after pancreatoduodenectomy but not after distal pancreatectomy. Further studies are required to determine whether neoadjuvant therapy should be added to post‐operative pancreatic fistula risk calculators.